2015
DOI: 10.1016/j.jpeds.2015.09.027
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Pediatric Severe Sepsis and Septic Shock: Accuracy of Diagnosis Codes

Abstract: Objectives To evaluate accuracy of two established administrative methods of identifying children with sepsis using a medical record review reference standard. Study design Multicenter retrospective study at six US children’s hospitals. Subjects were children >60 days and <19 years of age were identified in four groups based on ICD9-CM codes: (1) Severe sepsis/septic shock (Sepsis Codes); (2) Infection plus organ dysfunction (Combination Codes); (3) Subjects without codes for infection, organ dysfunction, or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 19 publications
2
38
2
Order By: Relevance
“…Second, using ICD-9-CM codes for infection plus organ dysfunction to identify pediatric sepsis is controversial. 17,18,36 Notably, patients with more specific ICD-9-CM sepsis codes had a trend toward decreased mortality and less dialysis in the LR group. Moreover, because identification and timing of surgical interventions is limited using administrative codes, it was difficult to fully account for a possible surgical preference to use LR.…”
Section: Discussionmentioning
confidence: 98%
“…Second, using ICD-9-CM codes for infection plus organ dysfunction to identify pediatric sepsis is controversial. 17,18,36 Notably, patients with more specific ICD-9-CM sepsis codes had a trend toward decreased mortality and less dialysis in the LR group. Moreover, because identification and timing of surgical interventions is limited using administrative codes, it was difficult to fully account for a possible surgical preference to use LR.…”
Section: Discussionmentioning
confidence: 98%
“…However, the consensus definition relies on laboratory data that may not be available in LMICs. In addition, the use of administrative data, as in this study, is associated with selection and reporting bias because of the challenges in disaggregating sepsis from severe sepsis due to the use of the ICD-10 code (26,27). Because administrative data were used in this study, the definition of sepsis may not necessarily meet the consensus criteria; hence, comparability with studies that used the consensus definition may be limited.…”
Section: Discussionmentioning
confidence: 99%
“…Sepsis was coded in the data set using the ICD-9 codes for severe sepsis (995.92) and septic shock (785.52). 9 Per Balamuth et al, 9 using the ICD-9 codes for severe sepsis and septic shock more accurately identified cases of pediatric sepsis compared to the use of ICD-9 combinations that include codes for both infections and organ failure ( Table 1).…”
Section: Methodsmentioning
confidence: 99%